Public relation for 21st century - Jović Tijana (Marketing (Beograd. 1991), 2005)
PR - Public relations has come of age, and with that has come a critical need for broadly-based education that is relevant and connected to the practice. The changes in public relations practice are numerous and profound. At root, these changes reflect nothing less than the way the world has changed and continues to change, seemingly spinning ever faster and veering in new directions. But, happily, the changes also reflect a broad acceptance of the validity of modern public relations practice to a global society that is increasingly interdependent, increasingly interconnected.